2019
DOI: 10.4187/respcare.07067
|View full text |Cite
|
Sign up to set email alerts
|

Cough Strength Is an Indicator of Aspiration Risk When Restarting Food Intake in Elderly Subjects With Community-Acquired Pneumonia

Abstract: BACKGROUND: The incidence of community-acquired pneumonia (CAP) is relatively high in elderly subjects. Cough peak flow (CPF) is an objective indicator of cough strength, and CPF evaluation might be useful to assess whether food intake can be restarted. We aimed to examine whether cough strength assessed with CPF can be used as an indicator of the aspiration risk when restarting food intake in elderly subjects with CAP. METHODS: This cross-sectional study included 82 elderly subjects with CAP between August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Hammond et al [8] conducted a research in patients with ischemic stroke to predict the aspiration risk using voluntary cough, and this was associated with an aspiration risk with a cut-off value of <2.9 L/s (=174 L/ min). Sakai et al [15] also suggested in their study that PCF could be used as an indicator to evaluate the aspiration risk in older adults with pneumonia, and the cut-off Pearson chi-square test. www.e-arm.org value was 190 L/min.…”
Section: Discussionmentioning
confidence: 99%
“…Hammond et al [8] conducted a research in patients with ischemic stroke to predict the aspiration risk using voluntary cough, and this was associated with an aspiration risk with a cut-off value of <2.9 L/s (=174 L/ min). Sakai et al [15] also suggested in their study that PCF could be used as an indicator to evaluate the aspiration risk in older adults with pneumonia, and the cut-off Pearson chi-square test. www.e-arm.org value was 190 L/min.…”
Section: Discussionmentioning
confidence: 99%
“…Cut-off values below 79 L/min predict respiratory complications with high accuracy [ 17 ]. In addition, cough strength, assessed by PCF, can be used to determine the aspiration risk when restarting food intake in elderly subjects with aspiration pneumonia [ 18 ]. In our second case, while the PCF level was below the suggested cut-off value in the initial assessment, the value increased in parallel with the mean peak RMS values by the time the patient was allowed to commence oral feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Swallowing function was evaluated using the repetitive saliva swallowing test (RSST), which showed sensitivity and specificity of 70.0% and 71.7%, respectively, in predicting aspiration [18]. A single trained dentist (S.A.) performed the RSST.…”
Section: Swallowing Functionmentioning
confidence: 99%
“…A swallow was counted only when the thyroid cartilage rose past the middle finger sufficiently. If such swallows were noted three consecutive times, the swallowing function was considered normal [18].…”
Section: Swallowing Functionmentioning
confidence: 99%